Korelasi Keterlaksanaan Praktikum dengan Keterampilan Berpikir Kritis pada Siswa SMA di Kota Pontianak - Aldiansyah, Rifki; Candramila, Wolly; Murdiyaningsih, Asriah Nurdini (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to describe the implementation of laboratory practices, assess students' critical thinking skills, and analyze the relationship between these aspects among senior high school students in Pontianak City who have adopted the Merdeka Curriculum. This research employs a survey method with a descriptive quantitative approach. The research instruments consist of a questionnaire and a test based on the five critical thinking indicators proposed by Ennis. Data were analyzed through normality, homogeneity, and heteroscedasticity tests, followed by Pearson correlation analysis to examine the relationship between variables. The results indicate that (1) the implementation of laboratory practices and (2) students' critical thinking skills fall into the "good" category, with scores of 70.59% and 73.40%, respectively. (3) Correlation analysis reveals a positive and significant relationship between the two variables, with a correlation coefficient of 0.920 (p = 0.02). Thus, it can be concluded that effective laboratory practices contribute to the enhancement of students' critical thinking skills.